Elektroniczna licytacja nieruchomości - Rogala, Krystyna (Wydawnictwo C.H. Beck, 2022)
Undoubtedly, the COVID-19 pandemic was an impulse for further informatization of civil proceedings, including mortgage foreclosure and bankruptcy proceedings. During the pandemic remote court hearings were introduced. The obligatory e-KRS for entrepreneurs and the National Register of Debtors were launched. Other examples of this legislative direction were introduced by the Act of 28 May 2021 amending the Act – Code of Civil Procedure and certain other acts like courts’ electronic service for professional attorneys, but also the regulation of the online judicial auction of real estate, long postulated by the doctrine. This study aims to discuss the introduced institution, also from the perspective of the regulation of electronic auctions of movable property and mortgage foreclosure according to general rules. The author also analyzes the regulation of the ICT system for electronic auctions of real estate as an ICT system supporting civil proceedings.
Keywords: informatyzacja postępowania cywilnego; elektroniczna licytacja nieruchomości; egzekucja z nieruchomości; platforma e-licytacje